Fresno State Women's Softball Team vs. UC Santa Barbara at Old Fenced Field - Watkins, Howard::::::::: (1988)
Fresno State batter #45 (Rogers) taking full swing; UCSB first baseman 12 feet away Visitors dugout behind chain linked fence; portable bleachers, and buildings in background